1991
DOI: 10.1128/iai.59.5.1872-1874.1991
|View full text |Cite
|
Sign up to set email alerts
|

Hemolytic and sphingomyelinase activities of Clostridium perfringens alpha-toxin are dependent on a domain homologous to that of an enzyme from the human arachidonic acid pathway

Abstract: The N-terminal domain of Clostridium perfringens alpha-toxin, homologous with the nontoxic phospholipase C of BaciUus cereus, was expressed in Escherichia coli and shown to retain all of the phosphatidylcholine hydrolyzing activity of the alpha-toxin, but not the sphingomyelinase, hemolytic, or lethal activities. The C-terminal domain of alpha-toxin showed sequence and predicted structural homologies with the N-terminal region of arachidonate 5-lipoxygenase, an enzyme from the human arachidonic acid pathway wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(54 citation statements)
references
References 25 publications
(17 reference statements)
2
52
0
Order By: Relevance
“…This was especially intriguing as phospholipases C are involved in the generation of arachidonic acid, which is converted into leukotrienes by arachidonate 5-lipoxygenase. Most prominent among the conserved amino acid residues were four tyrosines, and Titball has suggested that these could play an important role in recognizing substrate hydrocarbon chains (Titball et al, 1991;Titball, 1993). This is consistent with the finding that chemical modification of the tyrosine residues in ␣-toxin abolished its haemolytic and lethal activities as well as platelet aggregation (Sakurai et al, 1989).…”
Section: Introductionsupporting
confidence: 83%
See 3 more Smart Citations
“…This was especially intriguing as phospholipases C are involved in the generation of arachidonic acid, which is converted into leukotrienes by arachidonate 5-lipoxygenase. Most prominent among the conserved amino acid residues were four tyrosines, and Titball has suggested that these could play an important role in recognizing substrate hydrocarbon chains (Titball et al, 1991;Titball, 1993). This is consistent with the finding that chemical modification of the tyrosine residues in ␣-toxin abolished its haemolytic and lethal activities as well as platelet aggregation (Sakurai et al, 1989).…”
Section: Introductionsupporting
confidence: 83%
“…This region of ␣-toxin contains seven tyrosine residues, three of which are conserved in the C. bifermentans enzyme, four in C. novyi and four in lipoxygenase. Originally, five tyrosine residues were thought to be conserved in both lipoxygenase and ␣-toxin (Titball et al, 1991) but, from the refined alignment of clostridial phospholipases, it is now clear that there are only four ( Fig. 1).…”
Section: Replacement Of All Tyrosines In the C-terminal Domainmentioning
confidence: 99%
See 2 more Smart Citations
“…Three bacterial PLCs capable of hydrolyzing the major phospholipid of the E. coli cell membrane, phosphatidylethanolamine, 24 were selected for co-expression studies: the PLCs from B. cereus, L. monocytogenes and C. perfringens. [21][22][23] They were expressed in E. coli BL21(DE3), and their cell localization was investigated, except for that of B. cereus PLC, which was investigated in a previous study. 12 After L. monocytogenes PLC expression was induced in E. coli BL21(DE3) for 24 h, the extracellular and intracellular L. monocytogenes PLC activities were 7.5 U mL −1 and 0.3 U mL −1 , respectively.…”
Section: Recombinant Expression Of the Three Plcs In E Coli Bl21(de3)mentioning
confidence: 99%